Cross-cultural adaptation and validation of the Job Content Questionnaire (JCQ-22). - Quan, Liming; Wu, Lingyu; Zhang, Yang; Chen, Ting; Lan, Yajia (Work, 2023)
BACKGROUND: Although the Job Content Questionnaire (JCQ-22) has been translated into numerous languages and applied in various countries, its cultural applicability in China remains unclear. OBJECTIVE: To adjust the JCQ-22 for cross-cultural use and optimize the scoring method for suitability for Chinese working populations. METHODS: We first used the original JCQ-22 questionnaire to measure occupational stress. Cross-cultural adjustment involved reorganization of scale items (adjusted-I scale) and deletion of inefficient redundant items during reorganization of scale items (adjusted-II scale). Structural validity and the relationship between stress and health outcomes (insomnia and self-conscious symptoms) before and after adjustment were compared. RESULTS: Exploratory factor analysis revealed that the two-factor cumulative variance contribution rate of job demand and control of the adjusted-II scale was 52.47%, compared with 48.44% and 48.44% in the original version and adjusted-I scale, respectively. Among the 16 fitness indicators in confirmatory factor analysis, 9 items of the adjusted-II scale met the standard, compared with 4 items of the original and adjusted-I scales. The Pearson's correlation coefficients between occupational stress and insomnia as well as self-conscious symptoms from the adjusted-II scale were 0.15 and 0.32, respectively, which were higher than those of the original scale (0.10 and 0.20). Receiver operating characteristic analysis revealed that the adjusted-II scale exhibited a better area under the curve and Youden index values than the original scale. CONCLUSION: The adjusted-II scale exhibited superior structural validity with more reasonable health outcome predictions and fewer items, making it more suitable for measuring occupational stress in Chinese populations.